2013
DOI: 10.4236/ajps.2013.411275
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Polyamines and Trehalose in Wheat Microspores Culture for Embryogenesis and Green Regenerated Plants

Abstract: Most aspects of microspore culture protocol have the capacity to cause stress to microspores, hence, less stressful treatments might be required to avoid deleterious effects. In stressed plants, polyamines and trehalose can act as compatible solutes or osmoprotectants by stabilizing proteins and biological membranes. To improve green plant regeneration in wheat microspore culture, this study assessed the effects of polyamines (putrecine, spermidine, spermine) and trehalose on androgenic response namely embryog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The accumulation of compatible solutes is often regarded as a basic strategy for the protection and survival of cells under stressful conditions, including the stresses used for embryogenesis induction (Patnaik et al 2005;Chen et al 2007;Redha and Suleman 2013). According to our results, proline was not advantageous to microspore embryogenesis when maintained for 1 day in the induction medium, but a 30-55 % increase in the embryo formation was observed in response to 100 mg l -1 proline in the cultures incubated for 2 and 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of compatible solutes is often regarded as a basic strategy for the protection and survival of cells under stressful conditions, including the stresses used for embryogenesis induction (Patnaik et al 2005;Chen et al 2007;Redha and Suleman 2013). According to our results, proline was not advantageous to microspore embryogenesis when maintained for 1 day in the induction medium, but a 30-55 % increase in the embryo formation was observed in response to 100 mg l -1 proline in the cultures incubated for 2 and 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins and amino acids are the preferential organic nitrogen source in the culture media. Under stress condition plants tends to accumulate several metabolites and amino acids specially proline, which is a common strategy for the protection and survival of cells under such conditions including callus induction, green shoot regeneration and embryogenesis [ 53 – 55 ]. This study showed increment of green shoot regeneration in proline fortified media for all tested genotypes except IR20 X Mahulata.…”
Section: Discussionmentioning
confidence: 99%